Gene polymorphisms and response to transcranial direct current stimulation for auditory verbal hallucinations in schizophrenia. Issue 4 (21st March 2018) - Chhabra, Harleen; Shivakumar, Venkataram; Subbanna, Manjula; Kalmady, Sunil V.; Bose, Anushree; Agarwal, Sri Mahavir; Sreeraj, Vanteemar S.; Dinakaran, Damodharan; Narayanaswamy, Janardhanan C.; Debnath, Monojit; Venkatasubramanian, Ganesan
Abstract: Objective: Recent observations demonstrate a significant ameliorative effect of add-on transcranial direct current stimulation (tDCS) on auditory verbal hallucinations (AVHs) in schizophrenia. Of the many SNPs, NRG1 rs35753505 and catechol- o -methyl transferase (COMT) rs4680 polymorphisms have shown to have a strong association with neuroplasticity effect in schizophrenia. Methods: Schizophrenia patients ( n =32) with treatment resistant auditory hallucinations were administered with an add-on tDCS. The COMT (rs4680) and NRG1 (rs35753505) genotypes were determined. The COMT genotypes were categorised into Val group (GG; n =15) and Met group (GG/AG; n =17) and NRG1 genotypes were categorised into AA group ( n =12) and AG/GG group ( n =20). Results: The reduction in auditory hallucination sub-scale score was significantly affected by COMT-GG genotype [Time×COMT interaction: F (1, 28)=10.55, p =0.003, ɳ 2 =0.27]. Further, COMT-GG effect was epistatically influenced by the co-occurrence of NRG1-AA genotype [Time×COMT×NRG1 interaction: F (1, 28)=8.09, p =0.008, ɳ 2 =0.22]. Irrespective of genotype, females showed better tDCS response than males [Time×Sex interaction: F (1, 21)=4.67, p =0.04, ɳ 2 =0.18]. Conclusion: COMT-GG and NRG1-AA genotypes aid the tDCS-induced improvement in AVHs in schizophrenia patients. Our preliminary observations need replication and further systematic research to understand the neuroplastic gene determinants that modulate the effect of tDCS.